Consumer behavior towards Bata Shoe Company in Bangladesh: a study on customer satisfaction, brand loyalty, and buying patterns - Saquib, Mohammad Nazmus (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.